Technical report: finite difference method for solving one dimensional of shallow water equation / Farah Nabilah Samsudin, Nurul Fathiha Zakaria and Nur Atikah Nadhirah Maidin - Samsudin, Farah Nabilah; Zakaria, Nurul Fathiha; Maidin, Nur Atikah Nadhirah (2017)
Shallow Water Equation (SWE) also known as Saint-Venant equations. One-dimensional Saint-Venant equations are developed in order to simplify the Shallow Water Equations to a much simpler equations. These equations are solved using finite difference method which is one of the famous method that have been used by many researchers. The Shallow Water Equations are solved using the Crank-Nicolson method and the First Upwind Difference method. The purpose of this project are to solve one-dimensional shallow water equation by using finite difference methods and determine the velocity and the amplitude from the one-dimensional shallow water equations. Validation of the results are made using the Crank-Nicolson method and the First Upwind Difference method with Upwind Interpolation method.